First kidney transplantation in Chittagong Medical College Hospital - Chowdhury, Dipti; Yunus, Emran Bin; Kashem, MA; Dutta, Pradip Kumar; Huda, Md Nurul; Das, Saibal; Saha, Ratan; Rahman, Faijur; Saha, Joydeb; Deb, Alak; et al. (Journal of Chittagong Medical College Teachers’ Association, 2011)
DOI: http://dx.doi.org/10.3329/jcmcta.v22i1.9104 JCMCTA 2011; 22(1): 7-10